MicroRNA miR-29b regulates diabetic aortic remodeling and stiffening - Isabel N. Schellinger; Markus Wagenhäuser; Giriprakash Chodisetti; Karin Mattern; Angelika Dannert; Anne Petzold; Joanna Jakubizka-Smorag; Fabian Emrich; Josephina Haunschild; Andreas Schuster; Elisabeth Schwob; Kei Schulz; et al. (Elsevier, 2021)
Patients with type 2 diabetes (T2D) are threatened by excessive cardiovascular morbidity and mortality. While accelerated arterial stiffening may represent a critical mechanistic factor driving cardiovascular risk in T2D, specific therapies to contain the underlying diabetic arterial remodeling have been elusive. The present translational study investigates the role of microRNA-29b (miR-29b) as a driver and therapeutic target of diabetic aortic remodeling and stiffening. Using a murine model (db/db mice), as well as human aortic tissue samples, we find that diabetic aortic remodeling and stiffening is associated with medial fibrosis, as well as fragmentation of aortic elastic layers. miR-29b is significantly downregulated in T2D and miR-29b repression is sufficient to induce both aortic medial fibrosis and elastin breakdown through upregulation of its direct target genes COL1A1 and MMP2 thereby increasing aortic stiffness. Moreover, antioxidant treatment restores aortic miR-29b levels and counteracts diabetic aortic remodeling. Concluding, we identify miR-29b as a comprehensive-and therefore powerful-regulator of aortic remodeling and stiffening in T2D that moreover qualifies as a (redox-sensitive) target for therapeutic intervention.